Effect of Adding Aspergillus niger Mushroom on Patchouli Fermentation Process - Alivia Maulidina Pawestri; Noor Fitri (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
Indonesia is one of the biggest exporter country for essential oils in the world. One of Indonesia's essential oil export commodities is patchouli oil. Almost 90% of the world’s patchouli oil are exported from Indonesia. Various studies to improve the quality of Indonesian patchouli oil were carried out. In this research, the process of fermentation of patchouli raw material was conducted to enhance the quality of patchouli oil. Patchouli fermentation was carried out using A. niger. Preparation processes were carried out prior to distillation including withering, size reducing and fermenting. Patchouli was withered for 24 hours. Patchouli was cut into pieces and weighed as much as 800 grams (3 leaves: 1 stem) after withered. Patchouli fermentation was conducted anaerobically for 20 hours. Varying the addition of A. niger used was 5 mL, 10 mL, 15 mL and 25 mL mixed in 400 mL of distilled water. The amount of A. niger colonies was 8.8 x 105 /mL. Extraction of patchouli oil was performed by water bubble distillation. The chemical and physical properties of the patchouli oil were analyzed and compared to the quality standard of patchouli oil according to SNI 06-2385-2006. Chemical compound of patchouli oil was identified using GC-MS. The main compound of the patchouli oil is patchoulol. The GC-MS result indicates that patchoulol content increases with the increasing addition of A. niger. The content of patchoulol was detected up to 93.75 %w/w in patchouli oil. The optimal concentration of A. niger is 1.875% that produces the highest patchoulol content with an increase of up to 194.6 % compared to those of without A. niger (J0).